INFORMATION AS A FACTOR OF THE DEVELOPMENT OF ACCESSIBLE TOURISM FOR PEOPLE WITH DISABILITIES - Kołodziejczak, Anna (Quaestiones Geographicae, 2019)
Article describes access to tourist information and the consistency of tourist offers with this kind of information for people with disabilities. The conception of accessible tourism was presented as well as the model of tourist information availability with the demonstration of technology applied to ensure objective information about all services so as people with disabilities could evaluate the scope of accessibility according to their personal needs. Based on the analysis of information systems found on Internet tourist portals what is presented is the scope of information availability from the point of view of people with disabilities. These information systems largely contribute to the development of accessible tourism. In Poland, the issue of implementing the assumption of accessible tourism, including the availability of a coherent information system is an important challenge that requires integrated systemic activities of many entities.